Corporate governance and voluntary disclosure practices: evidence from a two tier board systems in Indonesia - Romlah Jaffar,; Dina Mardinah,; Azlina Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2013)
Lack of effective corporate governance mechanism and disclosure transparency frameworks have been partly blamed for the 1997-1999 East Asia economic crises. Consequently, Indonesia, together with many countries across the globe have been actively reviewing and improving their corporate governance and transparency mechanisms. Theoretically, corporate governance mechanism is designed to monitor and evaluate decisions made by managers in the management of a company to reduce agency cost and information asymmetry between the shareholders and the management. The main objective of the study is to examine the effect of corporate governance mechanism on the level of voluntary disclosure in Indonesia, a country that has adopted a two-tier board system. The two-tier board system is considered a better system compared to one tier board system since all members of the board are non-executives. Therefore, the board members are more independent and objective in supervising and monitoring the performance of executive managers. This study investigates four corporate governance variables which are expected to influence the level of voluntary disclosure; (1) composition of independent members of Board of Commissioners (BOC), (2) composition of family members on the BOC, (3) audit quality, and (4) managerial ownership. The sample consists of companies listed on Bursa Saham Indonesia for the year ended 2008. The influence of corporate governance on the level of voluntary disclosure is analyzed using multiple regression method. As expected, the results show that the compositions of independent BOC and auditor’s quality have a positive and significant relationship with the level of voluntary disclosure. Meanwhile, the composition of family members on the BOC has negatively influenced the disclosure. The results suggest that the corporate governance structure in a two-tier board system, specifically in Indonesia, is not significantly different from a one tier board system in influencing the level of voluntary disclosure.